Effect of climatic variables on rice yield and its forecast (MAUSAM, 1980)
An attempt has been made in this paper to study the effect of climatic variables on rice yield at different stages of crop growth as also to forecast rice yield using climatic variables. The results show that the crop reacts differently to climatic parameters during different stages of its growth. Above average maximum daily temperature is beneficial during active vegetative and ripening stages and detrimental during lag vegetative stage of the crop. A rise in relative humidity (at 7 hr) above average is beneficial during tillering and early part of reproductive stage but produces adverse effects during ripening stage. Above average relative humidity (at 14 hr) is beneficial during both early part of lag vegetative slap and later part of reproductive stage. The effect of increase in total weekly rainfall is in general beneficial throughout the crop season. Above average daily sunshine hour is beneficial during active vegetative and ripening stages but produces adverse effects in the lag vegetative and reproductive stages.The study on yield forecast shows that a reliable forecast is possible after about 2 months of sowing assuming weather to be normal after that. This as such calls for issuing revised forecasts periodically in case weather departs from normal.